(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The integration of Christian education and theology has an important role in shaping the character of the young generation in Toraja. Toraja society, which is rich in cultural traditions and Christian values, requires an approach that combines academic and spiritual aspects to create individuals who are not only intellectually intelligent, but also have noble character. Education in Toraja must involve in-depth teaching of Christian principles, such as love, honesty, and hard work, which can be applied to everyday life. Christian theology provides a strong moral foundation in developing positive attitudes and behavior among the younger generation. Through the synergy between formal education and religious teachings, it is hoped that the young Torajan generation can grow into individuals who are responsible, empathetic and have a high commitment to good and human values. Thus, this integration contributes to the formation of a strong and competitive character in the era of globalization